Mergers, Litigation and Efficiency - Oliver Gürtler; Matthias Kräkel (University of Bonn, Bonn Graduate School of Economics (BGSE), 2006)
We consider antitrust enforcement within the adversarial model used by the United States. We show that, under the adversarial system, the Antitrust Authority may try to prohibit mergers also in those cases in which litigation is ine? cient. Even if market concentration and technological disadvantages lead to a significant welfare reduction after merger, from societys perspective the agencys lawsuit may be ine? cient. We can show that these ine? ciencies may be aggravated if the takeover is hostile.
Keywords: L40; D43; K21; 330; hostile takeover; litigation contest; merger